Assessing quality attributes that drive preference and consumption of local rice in Ghana - Ayeduvor, Selorm (International Food Policy Research Institute, 2018)
Rice consumption in Ghana has more than quadrupled in the last 60 years, becoming a common staple food. However, this increasing demand is being met by imports. The rise in rice imports has led to a renewed interest in promoting domestic production of rice to substitute for imported rice. However, it is not clear how current rice development policies are informed by the preferences of consumers for specific quality attributes of rice. This study assesses the preferred rice qualities that drive consumption of local rice in Ghana. Through a review of previous studies on consumer preferences of rice complemented with information collected through interviews with local rice traders, millers, and other stakeholders, this paper describes the types of rice and their sources, the types of rice consumers, and the packaging and quality attributes of local rice in key markets in Ghana. We find that the quality of branded local rice types has improved in recent years. However, unbranded local rice in Ghana is still commonly contaminated with foreign materials, is made up of co-mingled varieties, and has a large share of broken and yellowish grain. In addition, local rice continues to be sold at a lower price than imported rice of same quality. This is largely due to the perceived low quality of local rice by consumers that results in low demand. Marketing campaigns and sensitization to advocate for consumption of local rice are recommended policy options to increase consumer awareness and to build demand for quality local rice in Ghana.